Pengembangan Media Mind Map Terintegrasi Lift The Flap Pada Materi Jaring-jaring Makanan Untuk Siswa Kelas V Sekolah Dasar - Fiska, Tiara; Feni Kurnia (Universitas Muhammadiyah Bangka Belitung, 2024)
The lack of learning media for science subjects, particularly food web material, inspired this study because schools have limited learning media, and using less varied media is still widespread. This research aims to develop an integrated lift-the-flap mind map learning medium on food web material at SD Negeri 12 Tempilang as a suitable and practical medium. This research is research and development (R&D) using the ADDIE model, which consists of 5 stages: analysis, design, development, implementation, and evaluation. The subjects of this research consisted of 24 fifth-grade students at SD Negeri 12 Tempilang. Data collection techniques and instruments are in the form of questionnaires. The data analysis technique is quantitative-descriptive, consisting of feasibility data from media and material experts. Practicality data was obtained from the results of student questionnaire responses. Based on the media validator assessment results, the percentage obtained was 92.45% (eligible), and the material validator obtained 87.5% (eligible). The results of small-scale trials were 95% (very practical), and those of large-scale trials were 97,80% (efficient). The results of the paired sample t-test have a significance value of 0.00 < 0.05, so it can be concluded that H0 is rejected and Ha is accepted, meaning that there are differences before and after in using learning media.